2022
DOI: 10.1039/d2ob00943a
|View full text |Cite
|
Sign up to set email alerts
|

Redox activated amines in the organophotoinduced alkylation of coumarins

Abstract: A metal-free photoinduced deaminative strategy for C-4 alkylation of coumarins using redox activated secondary and benzylic amine derived Katritzky pyridinium salts has been established and demonstrated efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Recently, Singh et al . reported the alkylation of coumarin‐3‐carboxylates by photocatalysis [13a,b] . Subsequently, Roy et al reported the alkylation of coumarin‐3‐carboxylates through a ligand‐to‐metal charge transfer (LMCT) approach by Lewis acid catalysis [13c] …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Singh et al . reported the alkylation of coumarin‐3‐carboxylates by photocatalysis [13a,b] . Subsequently, Roy et al reported the alkylation of coumarin‐3‐carboxylates through a ligand‐to‐metal charge transfer (LMCT) approach by Lewis acid catalysis [13c] …”
Section: Introductionmentioning
confidence: 99%
“…The emergence of photoredox chemistry in recent years was pioneered by the introduction of photocatalysts (PC) based on metals such as Ru and Ir [1][2][3][4][5][6]. However, due to the high cost and limited availability of precious metals, organic photocata-lysts have become a focal point of academic and industrial research [7][8][9][10][11][12][13][14][15]. Most of the established organic catalysts (acridinium salts [16][17][18][19], cyanoarenes [8,[20][21][22], quinones [23,24], etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Visible-light induced reactions have attracted extensive attention because of the advantages such as environmental friendliness, operational simplicity, and sustainability. , Aldehyde C–H bonds can be cleaved by hydrogen abstraction by radical species to generate acyl radicals. Such a radical-mediated S H 2 (homolytic bimolecular substitution) type hydrogen atom transfer (HAT) has excellent potential for site-selectivity .…”
Section: Introductionmentioning
confidence: 99%